The Influence of Learning Habits, Learning Facilities, and Family Environment on Learning Outcomes of High School Students in the Special Region of Yogyakarta Province - Zuyun Tawang Sari; Ahmad Hafidh Saiful Fikri Hall (International Journal of Educational Research, 2025)
The Effects of Study Practices, Learning Resources, and Home Environment on High School Students’ Academic Performance in Yogyakarta Province. Thesis. Yogyakarta: Faculty of Economics and Business, Yogyakarta State University. 2025. This research investigates how Study Practices, Learning Resources, and Home Environment affect the Academic Performance of high school students in Yogyakarta Province. It is classified as associative/causal research utilizing a quantitative methodology. The participants in this study included high school students from the Special Region of Yogyakarta Province. The sample comprised 160 respondents, selected through random sampling. Data were analyzed using SPSS software. The findings revealed the following: (1) Study Practices positively and significantly impact academic performance, demonstrated by a calculated t value greater than the t table (4.210 > 1.97529) with a significance level of 0.000, which is less than 0.05. (2) Learning Resources also show a positive and significant effect on academic performance, with a calculated t value exceeding the t table (2.306 > 1.97529) and a significance level of 0.022, which is less than 0.05. (3) The Home Environment positively and significantly influences academic performance, indicated by a t value greater than the table value (2.104 > 1.97529) and a significance level of 0.037, which is below 0.05. (4) Study Practices, Learning Resources, and Home Environment collectively have a positive impact on student academic performance, with a calculated F value exceeding the F table (42.608 > 2.66) and a significance level of 0.000, which is less than 0.05.